Correlation of hemoglobin levels with diabetic retinopathy in US adults aged ≥40 years: the NHANES 2005–2008 - Li, Xiao; Chen, Meirong (Frontiers in Endocrinology, 2023)
To explore the connection between hemoglobin levels and diabetic retinopathy (DR).Cross-sectional research used data from the National Health and Nutrition Examination Survey (NHANES) [2005][2006][2007][2008]. A multiple logistic regression analysis was done to investigate the association between DR and hemoglobin levels. Additionally, generalized additivity models and smoothed curve fitting were carried out.After adjusting for several covariates, there was a negative association between hemoglobin levels and DR in the study, which included 837 participants. The negative association between hemoglobin levels and DR was present in men and women， obese (BMI>30), and 60-69-year-olds in subgroup analyses stratified by sex, This is a provisional file, not the final typeset article BMI, and age. The association between hemoglobin levels and DR in the normal weight group (BMI<25) displayed an inverted U-shaped curve with an inflection point of 13.7 (g/dL).In conclusion, our research reveals that high hemoglobin levels are related to a decreased risk of DR.Ascertaining the hemoglobin levels ought to be regarded as an integral facet of the monitoring regimen for patients with diabetic complications and that the risk of DR is reduced through the detection and management of hemoglobin levels.